Transcription Factors as Novel Therapeutic Targets and Drivers of Prostate Cancer Progression - Xie, Kangzhe; Tan, Keely; Naylor, Matthew J. (Frontiers in Oncology, 2022)
Prostate cancer is the second most diagnosed cancer among men worldwide. Androgen deprivation therapy, the most common targeted therapeutic option, is circumvented as prostate cancer progresses from androgen dependent to castrate-resistant disease. Whilst the nuclear receptor transcription factor, androgen receptor, sustains the growth of prostate tumour during initial stage of the disease, androgen resistance is associated with poorly differentiated prostate cancer. In the recent years, increased research has highlighted the aberrant transcriptional activities of a small number of transcription factors. Along with androgen receptors, dysregulation of these transcription factors contributes to both the poorly differentiated phenotypes of prostate cancer cells and the initiation and progression of prostate carcinoma. As master regulators of cell fate decisions, these transcription factors may provide opportunity for the development of novel therapeutic targets for the management of prostate cancer. Whilst some transcriptional regulators have previously been notoriously difficult to directly target, technological advances offer potential for the indirect therapeutic targeting of these transcription factors and the capacity to reprogram cancer cell phenotype. This mini review will discuss how recent advances in our understanding of transcriptional regulators and material science pave the way to utilise these regulatory molecules as therapeutic targets in prostate cancer.